The Mediating Role of Social Sustainability in the Relationship between Community Participation and Support for Tourism - Begum Dilara Emiroglu (Journal of Tourism, Sustainability and Well-being)
This study aims to evaluate the perceptions of residents in Mardin, one of Turkey’s most significant cultural tourism destinations, regarding community participation, social sustainability, and support for tourism. The study also examines whether social sustainability mediates the relationship between community participation and support for tourism. In this context, data were collected from 617 residents using the convenience sampling method, and 537 of them were analyzed through reliability analysis, descriptive statistics, confirmatory factor analysis (CFA), and structural equation modeling (SEM). The results indicated that community participation negatively affects host-guest conflict and positively influences social acceptance. It was also found that community participation has no significant impact on social tolerance. Similarly, it was revealed that host-guest conflict negatively affects support for tourism, while social acceptance positively affects support for tourism. However, social tolerance was found to have no significant impact on support for tourism. Furthermore, the study revealed that host-guest conflict and social acceptance, as dimensions of social sustainability, mediate the relationship between community participation and support for tourism.